An Investigation of Exposure of Attending Referee Training Hockey Referees to Mobbing Behaviors and Their Zest for Work Levels: Example of Referees Attending University Education - Ali Yıldırım; Yunus Gür (Journal of Educational Issues, 2024)
In a study conducted for referees, it was concluded that existing training programs need to be complemented with content in the field of pedagogy and developmental psychology (Ploszaj et al., 2021). The aim of this study is to examine the zest for work levels of trained referees actively working for the Turkish Hockey Federation and the mobbing behaviors they are exposed to. A total of 99 hockey referees, 42 women and 57 men, participated in the study. The sample comprises of 5 International, 7 National, 45 Provincial and 42 Candidate referees. In the study, the “Mobbing Scale for Referees of Indoor Sports” developed by Hacıcaferoğlu (2014) was used to measure the mobbing behaviors that referees are exposed to and the “The Zest for Work Scale for Referees” developed by Erdoğan (2013) and adapted for referees by Karaçam and Pulur (2018) was used to measure the zest for work levels of referees. Shapiro-Wilk normality test was performed and it was seen that the data showed normal distribution. Frequency Analysis, Descriptive Statistics, Independent T-Test, One Way ANOVA and Correlation Analysis were used in SPSS 22.0 program to analyze the data. As a result of the study, it was determined that the referees’ zest for work scores and mobbing behavior scores were high. A statistically significant difference was found for female referees in the analysis of mobbing behavior scores according to gender variable (t = -2.294; p < .05). According to the one-way analysis of variance (ANOVA) results, the difference between the arithmetic means of the Mobbing Scale scores in terms of the referee classification variable was statistically significant (F = 4.876; p < .05). No significant difference was found as a result of the Pearson Correlation analysis performed to determine the direction of the relationship between the scales (r = .061; p > 0.05). As a result, it was seen that the zest for work scores of the referees were high, and female and candidate referees were more exposed to mobbing in terms of the exposure to the mobbing behaviors.